Validity and reliability test of screening questionnaires training movement appropriate to elderly people - Cerika Rismayanthi (MEDIKORA, 2020)
Increased age experienced by each person will end with the elderly age group, which is vulnerable to various activities due to physiological function decrease occurred. On the other hand, the elderly need to stay alive. Instead of socio-psychological aspects, muscular function, cardiovascular and balance, and mobility aspects are important factors that support our body's work. The assessment in this study uses the questionnaire of "Appropriate Movement for the Elderly" distributed to personal trainers or instructors for the elderly. The results of the validity test can be concluded that G4 (Press the arm in front of the chest) with r count = 0.176 0.666; G12 (Hyper-extension) with r count = 0.176 0.666; G14 (Ankle to left and right chest) with a value of r count = -0.78 0.666; G15 (Russian paver) with a calculated value of r = -0.78 0.666; G18 (Turn the arm clockwise) with a value of r count = 0.176; G36 (Cow Cat Attitude) with r count = - 0.14; G42 (Raise the sumo calf on the wall) with a calculated r-value = 0.176 0.666. Whilst, reliability test with Cronbach's Alpha value calculation was obtained at 0.734 0.60, which shows various types of movements are reliable or consistent. It can be concluded that the questionnaire about screening exercises that are suitable for the elderly prove is consistent for all questions and valid for 40 movements, while 7 other movements (pressing the arm in front of the chest, Hyper-extension, Knee wrists to the left and right chest, Russian paw, Turn the arm in the direction of the needle clock, Cow Cat Attitude, and Raise sumo, raise calf on the wall) were invalid or not suitable for physical activities in the elderly. Uji validitas dan reliabilitas kuesioner skrining gerakan latihan yang sesuai dengan lansia AbstrakPertambahan usia yang dialami oleh setiap orang akan berujung pada kelompok usia lansia, dimana rentan terhadap berbagai aktivitas karena adanya penurunan fungsi fisiologis yang terjadi. Di sisi lain, kebutuhan lansia untuk tetap dapat bertahan hidup harus dimiliki. Selain adanya aspek sosio-psikologis, aspek kemampuan otot, kardiovaskular dan keseimbangan serta mobilitas menjadi faktor penting untuk menunjang kerja tubuh. Pengukuran pada studi ini menggunakan kuesioner “Skrining Gerakan yang Cocok untuk Lansia” yang disebar kepada para personal trainer atau instruktur lansia. Diperoleh hasil uji validitas yang menyimpulkan bahwa G4 (Tekan lengan didepan dada) dengan r hitung = 0,176 0,666; G12 (Hiperektansi) dengan r hitung = 0,176 0,666; G14 (Pergelangan lutut ke dada kiri dan kanan) dengan nilati r hitung = -0,78 0,666; G15 (Puntir Rusia) dengan nilai r hitung = -0,78 0,666; G18 (Putar lengan searah jarum jam) dengan nilai r hitung = 0,176; G36 (Sikap Kucing Sapi) dengan nilai r hitung = - 0,14; G42 (Angkat sumo dan angkat betis di tembok) dengan nilai r hitung = 0,176 0,666. Sementara dalam uji reliabilitas diperoleh angka perhitungan nilai Cronbach’s Alpha 0.734 0.60, menunjukkan bahwa berbagai macam jenis gerakan yang ada termasuk reliabel atau konsisten. Dapat disimpulkan bahwa kuesioner mengenai skrining gerakan latihan yang sesuai dengan lansia terbukti konsisten dalam pemberian pertanyaan dan valid sebanyak 40 gerakan, sedangkan 7 gerakan lainnya (Tekan lengan didepan dada, Hiperektansi, Pergelangan lutut ke dada kiri dan kanan, Puntir Rusia, Putar lengan searah jarum jam, Sikap Kucing Sapi, dan Angkat sumo angkat betis di tembok) tidak valid atau tidak cocok untuk dilakukan oleh lansia saat beraktivitas fisik.